“Embracing a Borrowed Life”: A Narrative Analysis of Post-Transplantation Experiences among Indian Kidney Recipients - Naveen Kumar; Archita Tandon; Rashmi Rana; Mohinder Pal Sachdeva; Anurag Gupta; Devinder Singh Rana (Indian Journal of Public Health, 2025)
This study systematically examined the multifaceted dimensions of the posttransplantation experiences of Indian kidney recipients through a meticulous narrative analysis of clinical interview data sourced from 111 male and 28 female recipients. The mean age of recipients was 39.63 ± 11.61 years, while donors exhibited a mean age of 48.68 ± 11.81 years. A predominant 33.8% of all donors were identified as maternal contributors. A central thematic construct, “fear of graft rejection,” emerged from the data. Subsequently, five subordinate themes were discerned: (i) Maintenance immunosuppressants and disease vulnerability, (ii) Translating gaze as nazar (evil eye), (iii) Decisions within families, donations by women, and (iv) Graft as a gift of life. This comprehensive elucidation of the recipients’ perspectives augments the scholarly comprehension of the intricate challenges and decision-making processes inherent in the landscape of Indian kidney transplantation, characterized by a preponderance of living donations within familial networks.